ANALYSIS OF HYDROPOWER RESOURCES OF UZBEKISTAN - Uzbekov Mirsoli Odiljonovich; Sanjarbek Rakhmonjonovich Ormonov (Western European Studies, 2024)
The increasing global demand for electricity has significantly raised the consumption of hydrocarbon fuels in energy production. This article explores Uzbekistan's energy sector, emphasizing the need for diversifying energy sources and utilizing renewable energy, especially hydropower. It provides insights into Uzbekistan’s current energy challenges, its hydropower potential, and strategic state policies aimed at promoting sustainable energy production.
Keywords: Hydropower potential; diversification; energy capacity